Valorization of Cascara coffee waste as antimicrobial edible coating for enhancing the snake fruit quality - Salsabila Luqyana Rachmat; Kayla Azzahra N; Layla Hawa Sahda Zabrina; Dwi Yuni Hastati (Bioculture Journal, 2026)
Background: This study explores a strategy to decrease significant post-harvest losses due to spoilage. Edible coating on fruit can help maintain its quality and extend shelf life by slowing physiological processes such as respiration and transpiration. Method: The coating was formulated divided into two formulas, one is fresh cascara coating while other is dried cascara coating that was obtained by drying at 60 °C for 4 hours. Both 300 grams of cascara were extracted by maceration with 96% ethanol (ratio 1:2) for 24 hours. Extracts were mixed with 2.5% (w/v) chitosan solution, 4 g glycerol, and 0.1% Tween 80, then homogenized using a magnetic stirrer. Washed and air-dried snake fruit fruits were dipped in the coating solution, dried at 50 °C for 30 minutes. The coating formulation included food grade glycerol as a plasticizer and was applied using a dipping method. Snake fruit that has been coated with the solution stored at room temperature and evaluated for its shelf life and antimicrobial activity. Finding: This research utilized cascara extract as the main ingredient of an edible coating applied to snake fruit. As a result, cascara can be used into functional materials since it has been investigated as a natural source of bioactive compounds, particularly phenolics, with notable antimicrobial potential and bioactive content of polyphenols. When applied as a snake fruit coating, cascara-based edible coating can inhibit microbial growth and extend shelf life while maintaining fruit quality. Conclusion: This approach can be applied to underutilized by-products from coffee beans, reducing dependency on synthetic preservatives and plastics while also offering a promising alternative for antimicrobial edible coating to promote valorization, circular economy practices, and innovation in food packaging. Novelty/Originality of this article: This research introduces a novel application of coffee cherry by-products (cascara) specifically formulated for snake fruit (Salacca zalacca), a tropical commodity with unique preservation challenges.